1998
DOI: 10.1002/(sici)1096-9861(19980330)393:1<84::aid-cne8>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of serotonin in the developing superior colliculus alters the normal development of the uncrossed retinotectal projection

Abstract: A previous study from this laboratory showed that sprouting of serotoninergic axons in the hamster's superior colliculus (SC) induced by a single subcutaneous injection of 5,7-dihydroxytryptamine (5,7-DHT) at birth (postnatal day 0; P-0) resulted in an abnormal terminal distribution of the uncrossed retinotectal projection. The present study provided further evidence to support the role of increased 5-HT levels within the SC in this phenomenon. Slow-release polymer (ELVAX) chips impregnated with serotonin (5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Numerous studies have suggested that, in addition to its actions as a neuromodulator in adult nervous systems, serotonin plays important roles in the development of neuronal circuits. For example, serotonin influences process outgrowth and synapse formation (Haydon et al, 1984;Goldberg and Kater, 1989;Diefenbach et al, 1995;Mercer et al, 1996), and the manipulation of serotonin levels during development alters the structure and function of identified neurons and connections (Mooney et al, 1998;Persico et al, 2000;Sullivan et al, 2000;Benton and Beltz, 2001). This suggests that serotonin might play a developmental role in the stomatogastric nervous system at the time it first appears, around the second larval stage.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have suggested that, in addition to its actions as a neuromodulator in adult nervous systems, serotonin plays important roles in the development of neuronal circuits. For example, serotonin influences process outgrowth and synapse formation (Haydon et al, 1984;Goldberg and Kater, 1989;Diefenbach et al, 1995;Mercer et al, 1996), and the manipulation of serotonin levels during development alters the structure and function of identified neurons and connections (Mooney et al, 1998;Persico et al, 2000;Sullivan et al, 2000;Benton and Beltz, 2001). This suggests that serotonin might play a developmental role in the stomatogastric nervous system at the time it first appears, around the second larval stage.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it would be valuable to distinguish hippocampal connections using in vivo imaging methods. This rationale is reinforced by tracer studies in animals showing that individual hippocampal neurons rarely contribute axons to both the precommissural and postcommissural fornix ( Donovan and Wyss, 1983 , Naber and Witter, 1998 ).…”
Section: Discussionmentioning
confidence: 99%
“…The serotonergic transmitter system modulates many physiological functions such as mood, sexual behavior, feeding, sleep/wake cycle, memory, cognition, blood pressure regulation, breathing, and reproductive success (Mooney et al, 1998; Abrams et al, 2004; Lechin et al, 2006; Lerch-Haner et al, 2008; McDevitt and Neumaier, 2011). Because of the complexity and variety of the different behaviors modulated by serotonin, it is expected that modulatory signals from other brain areas including sensory information is integrated by GPCR signals in nuclei containing 5-HT neurons using a high diversity of GPCRs.…”
Section: Integration and Signal Processing Of Modulatory Information mentioning
confidence: 99%